An smart toilet integrated performance detection device combined with machine vision. Issue 2 (April 2021) - Feng, Panpan; Chen, Zhuo Liang; Chen, Tianyu; Xu, Hua
Abstract: The traditional smart toilet comprehensive detection device proves unsatisfying on integration, intelligence, time and effort cost, and precision. In order to improve the detection accuracy and efficiency of smart toilets test, and overcome the poor integration of equipment and low intelligence, image processing technology is applied to the comprehensive performance detection equipment for smart toilets in this paper. Lenovo all-in-one computer is used as the upper computer to realize the collection and analysis of key data. Siemens PLC, as a lower-level computer, controls multiple temperature water tanks, frequency converters and pipeline valves, and collects and transmits data on temperature and cleaning power. Meanwhile, CCD camera is innovatively introduced to locate the seat temperature test points on the smart toilet. The test results show that the detection accuracy, efficiency and integration of the device are improved obviously.